EVALUATION OF THE RELATIONSHIP BETWEEN LIGHT USE EFFICIENCY AND SOLAR RADIATION IN POTATO - Praharaj, C. S.; Govindakrishnan, P M; Rawat, Shashi; Lal, S S. (Potato Journal, 2013)
A study was conducted to test the accuracy of estimated total dry weight of potato calculated from intercepted radiation and light use efficiency (LUE) derived as a function of irradiance. The data were from growth analyses experiments involving six widely grown Indian potato cultivars viz., Kufri Chandramukhi, Kufri Ashoka, Kufri Pukhraj, Kufri Jyoti, Kufri Sindhuri and Kufri Lalima, planted on two dates for 3 years and sampled periodically at ten days interval starting from 30 days after planting. The results revealed good correspondence between observed and estimated values of total dry weight when the LUE values were adjusted for the irradiance.